INVESTIGATING THE ROOT CAUSES OF THE RISING MENTAL HEALTH ISSUES AMONG GENERATION Z - Daffa Hegian Abiy Ahmed; Tias Sekar Sari; Rizqina Ritnaning Febriyanti; Najwa Aulia Zahra (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to examine the root causes of the increase in cases of mental disorders in Generation Z, a demographic group born between 1997 and 2012, and known to be very familiar with the digital world. Mental disorders are defined as health conditions that affect a person's thoughts, feelings, or responses, including anxiety, depression, and stress that can cause physical symptoms. Determinants of mental health include socioeconomic, biological, and environmental aspects. Compared to previous generations, Gen Z shows higher levels of stress, anxiety, and depression. This study uses a literature review method, analyzing and summarizing previous studies from trusted academic databases such as Google Scholar, Sinta, and Garuda with keywords such as